Peran Wisata Air terhadap Perkembangan Pariwisata diKabupatenKlaten - , HIDAYAT SAPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Klaten regency is one of regencies in Central Java, presenting various types of tours that can be enjoyed by tourists. Type of tourism in Klaten regency include: nature, water tourism, cultural tourism, and artificial tourist. Type water tourism is one of the most tourist visited by many tourists. Based on this phenomenon then conducted research to answer the purpose, among others, determine the tourism potential of water in Klaten, knowing water tourism contribution to local revenues of the tourism sector, knowing the role of government in the management and development of water tourism, as well as determine the direction of development of tourism potential water located in the district of Klaten. The method used is descriptive method of secondary and primary data types. Types of secondary data